(untitled) (Journal of Architectural Design, 2022)
Termez is the southernmost city of Uzbekistan, the administrative centre and the largest city of the Surkhandarya vilayat. It is one of the oldest cities in Central Asia and Uzbekistan - it is over 2500 years old. In 2014, Termez was awarded the Order of Amir Temur. The article explores the most important sights of Termez: the Termez Archaeological Museum and Buddhist statues.